Association of phosphorylation status of ERK and genetic MAPK alterations in pediatric tumors - Florian Selt; Romain Sigaud; Andrey Korshunov; David Capper; David Reuss; Andreas von Deimling; Kristian W. Pajtler; Cornelis M. van Tilburg; Martina Nesper-Brock; David T. W. Jones; Stefan M. Pfister; Felix Sahm; et al. (Scientific Reports)
Abstract The mitogen-activated protein kinase (MAPK) pathway is one of the most frequently altered pathways in pediatric cancer. Activating genomic MAPK-alterations and phosphorylation of the MAPK downstream target ERK (pERK) were analyzed in the PTT2.0 registry to identify potential targets for MAPK-directed treatment in relapsed pediatric CNS tumors, sarcomas and other solid tumors. The present study investigates the association of ERK phosphorylation and genomic MAPK pathway alterations (mutations, fusions, amplifications) in the PTT2.0 dataset. PTT2.0 registry cases with available genomic and immunohistochemistry data (n = 235) were included. Samples with and without detected activating genomic MAPK alterations were compared regarding ERK phosphorylation, quantified by immunohistochemistry H-score. The association of pERK intensity and the presence of MAPK alteration was analyzed using a univariable binary logistic regression model.The mean pERK H-score was significantly higher in samples with activating genomic MAPK alterations. pERK H-score positively correlated with the presence of MAPK alterations. However, the pERK H-score predicted MAPK alterations only with a sensitivity of 58.3% and a specificity of 83.8%. The highest mean pERK H-scores were observed in low-grade gliomas, enriched for MAPK alterations, and in ependymoma, where MAPK alterations were absent. Although there is an association between pERK level and activating genetic MAPK alterations, the predictive power of pERK H-score for genetic MAPK alterations is low in pediatric tumors. Tumors/groups with absent genetic MAPK alterations but high pERK indicate a dissociation of the two parameters, as well as a possible MAPK pathway activation in the absence of genetic MAPK alterations.